PELATIHAN PEMBUATAN PLATFORM MARKETPLACE PRODUK KERAJINAN TANGAN KEWIRAUSAHAAN SISWA SMK KOLESE TIARA BANGSA BATAM - Elisa, Erlin; Darmansyah , Darmansyah; Zetli, Sri; Simanjutak , Pastima; Satria, Robby (PUAN INDONESIA, 2025)
Digital sales in Indonesia have become increasingly accessible with the presence of electronic payment systems such as digital wallets (e-wallets) and online bank transfers, which simplify transactions between buyers and sellers. Social media platforms like Instagram, Facebook, and TikTok have become effective marketing tools, enabling brands to reach a wider audience through targeted advertisements and influencer marketing. E-commerce in Indonesia has also seen significant growth, with platforms such as Tokopedia, Bukalapak, Shopee, and Lazada dominating the market. The training on marketplace development in E-Commerce for students of SMK Kolese Tiara Bangsa Batam aims to provide practical skills in designing and developing effective online buying and selling platforms. Students will learn the basic concepts of E-Commerce. This training also covers payment system management, product catalog organization, as well as key aspects related to data security and online transactions. Through this training, students are expected to acquire the necessary skills to build a professional marketplace for marketing handcrafted products and student entrepreneurship, as well as understand the fundamental principles of digital marketing and how to attract customers in the E-Commerce landscape.